FENOMENA SEKS PRANIKAH DI KALANGAN PEMUDA BERPENGHASILAN (Studi Kasus di Denpasar) - Renanda, Kevian; Astika, Ketut Sudhana; Tamim, Imron Hadi (JURNAL ILMIAH SOSIOLOGI (SOROT), 2015)
ABSTRACT Balinese culture, especially the young adult comunity in Denpasar in particular is the result of the long process of assimilation and acculturation. The influx of new modern cultural that goes to Bali have been pervasive in the various aspect ofÂ  peoples lives in Bali, including the pattern of living among young adults, modern lifestyle and consumerism. This research aims to know the factors that affect the behavior of adolescent to young adults related to premarital sex in Denpasar, and how to prevent premarital sex behaviors that are currently already a considerable problems if not immediately resolved. The subjects of this study are some young adults who each earn an income in Denpasar which is indeed identified. The technique of data collection conducted in this study is an in-depth interview, observation technique used in this study using a non participant observation, where researchers did not directly involved in the activities of the subject. From the results of data analysis, it showed that premarital sex behaviors in young adults in Denpasar have several factors that can be affected, such as the influence of peers, age in puberty stage, economic status, social control and lowself concept in their selves. There are several suggestions to prevent premarital sex behaviours among young adults in Denpasar i.e. by choosing good peers and listen to what the parents told limit the young adults sex desires and strengthen the values of religion and education. Â  Key words: Young adult, Premarital Sex, Income Earners.